Design Of Inventory Data Information Systems In PT. Matahari Putra Prima. Tbk - Saryani, Saryani; Harfizar, Harfizar; Maulana, Julio Fahmi (Pandawan, 2019)
The development of technology that is developing at this time attracts a lot of public attention. Information technology as not important to run a business, therefore a computerized system is one of the supporting business success. Because with a computerized system can facilitate its use in carrying out activities or activities. The development of computers that continues to be dynamic and requires information that is fast, precise and systematic and does not require a long time. Computers have become the main tool in every human activity. Not only for business applications, but also in the daily activities of each company. This shows how computers have become part of human renewal of technology. Especially the inventory system of important items for the sales process at PT. Matahari Putra Prima Tbk in terms of inventory fields. Where still using the bookkeeping system. Data processing is still manually using Microsoft Excel and often occurs less accurate in inputting, with errors that occur when recording data items in and out so that data inventory items are ineffective and inefficient. With less than maximum, an inventory of goods data will be moved from the information needed by the customer or leader. And this research uses system design implemented with Unified Modeling Language (UML). This is the rationale for how the author analyzes the data inventory system of goods that exist in PT. Matahari Putra Prima Tbk can make it easy to input inventory data to get efficient and accurate reports.